2017
DOI: 10.1371/journal.pone.0187495
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Mortality in Emergency Department Sepsis Score, Modified Early Warning Score, Rapid Emergency Medicine Score and Rapid Acute Physiology Score for predicting the outcomes of adult splenic abscess patients in the emergency department

Abstract: BackgroundSplenic abscess is rare but has mortality rates as high as 14% even with recent improvements in management. Early and appropriate intervention may improve patient outcomes, yet at present there is no identified method that can predict mortality risk rapidly and accurately for emergency physicians, surgeons, and intensivists to decide on the ideal course of action.ObjectiveThis study aims to evaluate the performance of Mortality in Emergency Department Sepsis Score (MEDS), Modified Early Warning Score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 21 publications
(19 reference statements)
0
20
0
2
Order By: Relevance
“…This scale includes four parameters: blood pressure, pulse, respiratory frequency, and Glasgow coma scale (GCS) score. [24][25][26]. However, the predictive ability of the RAPS differs among disease types.…”
Section: Resultsmentioning
confidence: 99%
“…This scale includes four parameters: blood pressure, pulse, respiratory frequency, and Glasgow coma scale (GCS) score. [24][25][26]. However, the predictive ability of the RAPS differs among disease types.…”
Section: Resultsmentioning
confidence: 99%
“…MEDS has also been demonstrated to be a good predictor of prognosis in patients with other intra-abdominal infections [19, 21, 22] and even performs better than other more established risk assessment tools including APACHE II and quick Sepsis-related Organ Failure Assessment in determining mortality risk of ED patients in infection and/or sepsis [2330]. Its superiority in this study provides further evidence that both clinical presentation and patient characteristics are significant in assessing mortality risk of patients with abdominal infections as mentioned in our introduction, almost half of the 9 criteria in MEDS (age, nursing home resident, terminal illness, altered mental status) are dependent on the patient's medical history that is easily and quickly ascertainable in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis results demonstrated that MEDS was superior to MEWS, REMS, and RAPS, thus giving merit to the hypothesis that patient characteristics should also be considered in patients with abdominal infections. We were however surprised to note that the performance of REMS in predicting mortality of splenic abscess patients was ranked last [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Najafi, Zakeri, & Mirhaghi (2018) juga meneliti scoring REMS untuk prediksi outcome pada populasi trauma menemukan nilai AUC 0,92 atau performa sangat baik. Nilai ini berbeda dari penelitian Hung, et al (2017)yang menyebutkan prediksi mortalitas pasien sepsis di IGD mendapatkan AUC sebesar 0,67 atau performa cukup.…”
Section: Pembahasanunclassified
“…Nilai cut of point optimal >5 (risiko sedang) digunakan untuk memprediksi outcome pasien trauma kepala di IGD dengan sensitivitas 61,38%, spesifisitas, 77,78%. Hasil ini tidak jauh berbeda dari hasil penelitian oleh Park, et al (2017) yang memperoleh cut off point optimal 7 (risiko sedang) dengan sensitivitas 84,4%, spesifisitas 77,3%, juga Hung, et al (2017) memperoleh nilai cut off point optimal 7 (risiko sedang) dengan sensitivitas 64,29%, spesifisitas 72%. Adanya kemiripan nilai cut off point optimal yang diduga skor awal berisiko dan berdampak pada outcome yang buruk ini menunjukkan bahwa parameter REMS mampu memprediksi outcome pasien trauma kepala pada semua penelitian.…”
Section: Pembahasanunclassified